The Indonesian Government Imagery in the Instagram Comic strip with Covid-19 Themed - Pratama, D M; Kasmana, K (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
At the beginning of 2020, there has been the spread of the deadly Covid-19 virus to various countries resulted in a pandemic. Indonesia is one of the countries affected, so the government provides a policy that is expected to reduce the number of Covid-19 cases. The policy issued has drawn criticism from various parties, one of which is the cartoon mice comic, this comic is one of the comics that often comments on social life and the Indonesian government with its comic strips posted on Instagram. This study aims to find the image and role of the government depicted in mice cartoon comics in overcoming Covid-19 in Indonesia, therefore there is a need for analysis and research with descriptive methods and critical discourse analysis approaches to see how the image of the Indonesian government in comic mice cartoons. The results of the analysis of the two comics concluded that the image of the government displayed in the comic strip did not only come from the author’s idea but also based on the news that emerged from the government’s response to the spread of the Covid-19 virus in Indonesia, with an image style that was distinctive from mice cartoon comics. With this research, the researcher hopes that it can become a recommendation in making comic narratives, especially those discussing social life and government, and can be a reference for research that has the same object.